PENGUATAN KEMAMPUAN BERNALAR KRITIS SISWA MELALUI PROYEK KLIPING KARAKTERISTIK WILAYAH PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS V SD - Dini Putri Zahara; Philsa Arin Pateka; Tihan Arvita; Resyarusyda Parandrengi (STKIP Subang, 2026)
The low level of critical thinking skills among students in Pancasila Education classes is one of the issues identified in Grade 5 at SD Negeri 111/I Muara Bulian. Students tend to memorize the material and struggle to analyze and connect the information to real-life situations. This study aims to describe the implementation of the Project-Based Learning (PjBL) model through a regional characteristics scrapbook project and to determine the improvement in the critical thinking skills of fifth-grade students. The method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model. The research subjects consisted of 17 fifth-grade students at SD Negeri 111/I Muara Bulian. Data collection techniques included observation, interviews, tests, and documentation, which were then analyzed quantitatively and qualitatively. The results of the study indicate an improvement in students’ critical thinking skills following the implementation of the Project-Based Learning model. The students’ average score in the pre-intervention phase was 62.35 with a mastery rate of 29.41%, which then increased to 84.71 with a mastery rate of 88.24% in Cycle I. The regional characteristics clipping project proved capable of encouraging students to be more active in seeking information, discussing, analyzing the relationship between geographical conditions and community life, and drawing conclusions based on the facts discovered. Thus, it can be concluded that the implementation of the Project-Based Learning model through a project on regional characteristics is effective in improving students’ critical thinking skills in Pancasila Education classes for fifth-grade students at SD Negeri 111/I Muara Bulian.